Ukuran Perusahaan, Profil Industri dan Intensitas Pengungkapan Sustainability Reporting pada Perusahaan Pemenang Environmental, Social, Governance Awards - Adnyaswari, I Dewa Ayu; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p02, 2023)
This study aims to determine the effect of company size and industry profile on the intensity of disclosure of sustainability reporting. The research population is 119 companies that won the Environmental, Social, Governance (ESG) Awards. The sample selection used a purposive sampling technique and a sample of 72 companies was obtained during the study period. The analysis technique used in this research is multiple linear regression analysis. The results of the study state that company size has a positive effect on the intensity of disclosure of sustainability reporting and industry profile also has a positive effect on the intensity of disclosure of sustainability reporting in companies that win ESG Awards. Keywords: Firm Size; Industry Profile; Sustainability Reporting Disclosure Intensity.